Influence of dissolved gasses in epoxy resin on resin infusion part quality. (May 2020) - van Oosterom, Sam; Schreier, Aigoul; Battley, Mark; Bickerton, Simon; Allen, Tom
Abstract: This study investigates the influences of dissolved gasses on vacuum assisted resin infusion, providing a methodology which can be applied to assist in the development of robust high-performance infusion manufacturing processes. Resin degassing pressure was found to be influential on the effectiveness of degassing. Pressures under 5 mBar are recommended to ensure rapid and thorough removal of dissolved gasses. The saturation point of dissolved oxygen in resin was found to linearly correlate with resin pressure. The binary saturation condition of the resin during vacuum assisted resin infusion processes was found to directly impact void content within a cured laminate. Resin that was oversaturated with dissolved gas relative to the set post-fill fluid pressure was found to result in average void contents ranging from 1 to 2% across the laminate. Undersaturated resin resulted in consistently low void contents, being less than 0.2% across the laminate. This demonstrates the significance of resin dissolved oxygen content.